Mengharmonisasikan Manusia dan Alam: Kajian Filsafat Relasionalitas Armada Riyanto atas Kejadian 2:6-16 - Sekundus Septo Pigang Ton (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
The writing of this article focuses on Harmonizing Man and Nature: Armada Riyanto's Relationality Philosophy Study on Genesis 2:6-16. The current ecological crisis is caused by human over-exploitation, such as mining, deforestation, factory waste into rivers and plastic waste. The purpose of writing this article is to harmonize nature and humans who have been destroyed by the ecological crisis. The findings are first, the similarity of the word 'Ādam םדא (Human) with the word המדא Adamā (Land) as a relation of "I and Reality (Phenomenon)" gives an understanding that humans come from the land. To destroy the soil is to destroy oneself. Second, the Garden of Eden (ןֶֶדֶג-ןַּג, Gan' Eden) as a space of subjectivity, namely the existential experience of the first human, and the teaching of Eco-Ethics for modern humans to act as subjects within its scope. Third, the tree of knowledge ַןַעהַַּ ַּןַּע (Etz Hada'at) and the river as a "Lifeworld" space have double meanings. The method used is literature review with descriptive analysis and hermeneutic exegesis.AbstrakPenulisan artikel ini berfokus pada Mengharmonisasikan Manusia dan Alam: Kajian Filsafat Relasionalitas Armada Riyanto atas Kejadian 2:6-16. Krisis ekologi yang terjadi saat ini disebabkan ulah manusia yang mengeksploitasi secara berlebihan, seperti pertambangan, deforestasi, limbah pabrik ke sungai dan sampah plastik. Tujuan dari penulisan artikel ini adalah mengharmonisasikan alam dan manusia yang telah hancur akibat kurasakan ekologi. Temuannya adalah pertama, kesamaan kata 'Ādam אדם (Manusia) dengan kata אדמה Adamā (Tanah) sebagai relasi “Aku dan Realitas (Fenomena)” memberi pemahaman bahwa manusia berasal dari tanah. Merusak tanah berarti merusak diri sendiri. Kedua, Taman Eden (גן־ ֶעֶ דֶן , Gan 'Eden) sebagai ruang subjektivitas yakni pengalaman eksistensial manusia pertama, dan ajaran Eco-Etika bagi manusia modern untuk bertindak sebagai subjek dalam ruang lingkupnya. Ketiga, pohon pengetahuan ֵעֵץ ה ד עת (Etz Hada'at) dan sungai sebagai ruang “Lifeworld” memiliki double makna. Metode yang digunakan adalah kajian pustaka dengan analisis deskriptif dan hermeneutika eksegesis.